Agents of change among people living with HIV and their social networks: stepped-wedge randomised controlled trial of the NAMWEZA intervention in Dar es Salaam, Tanzania. Issue 3 (9th May 2019) - Smith Fawzi, Mary C; Siril, Hellen; Liu, Yuanyuan; McAdam, Keith; Ainebyona, Donald; McAdam, Elspeth; Somba, Magreat; Oljemark, Kicki; Mleli, Neema; Lienert, Jeffrey; Andrew, Irene; Haberlen, Sabina; et al.
Abstract : Introduction: NAMWEZA is a novel intervention that focuses on preventing HIV and promoting sexual and reproductive health and rights by addressing underlying factors related to vulnerability of acquiring HIV, such as depression, intimate partner violence (IPV) and stigma. The goal of the study was to evaluate the effect of the NAMWEZA intervention on risk behaviour as well as factors potentially contributing to this vulnerability for people living with HIV and their network members. Methods: A stepped-wedge randomised controlled trial was conducted from November 2010 to January 2014 among people living with HIV and their network members in Dar es Salaam, Tanzania. 458 people living with HIV were randomised within age/sex-specific strata to participate in the NAMWEZA intervention at three points in time. In addition, 602 members of their social networks completed the baseline interview. Intention-to-treat analysis was performed, including primary outcomes of uptake of HIV services, self-efficacy, self-esteem, HIV risk behaviour and IPV. Results: For people living with HIV, a number of outcomes improved with the NAMWEZA intervention, including higher self-efficacy and related factors, as well as lower levels of depression and stigma. IPV reduced by 40% among women. Although reductions in HIV risk behaviour were not observed, an increase in access to HIV treatment was reported for network members (72% vs 94%, p=0.002). Conclusion: These results demonstrate the complexity of behavioural interventions in reducing the vulnerability of acquiring HIV, since it is possible to observe a broad range of different outcomes. This study indicates the importance of formally evaluating interventions so that policymakers can build on evidence-based approaches to advance the effectiveness of HIV prevention interventions. Trial registration number: NCT01693458 .